Mobilizing Society for Peace: Enhancing Access to Justice of Tribal Dispute Resolution in Baduy and Sasak Tribes, Indonesia - FADLI, Moh; HADIYANTINA, Shinta; CAHYANDARI, Dewi; LIEMANTO, Airin; LUTFI, Mustafa (Revista Jurídica Portucalense, 2024)
In the last few decades, social, cultural, economic, and political conflicts have been on the rise. People need the existence of an institution to get access to justice and reconciliation for peace. However, judicial systems in Indonesia for some fail to accommodate the justice parallel to people’s expectation. This research is aimed at delineating the uniqueness of adat (tribal) dispute resolutions, particularly in Baduy and Sasak tribes in comparison to district courts in responding to issues and accelerating peace. This research employed a socio-legal method, FGD, and in-depth interviews. The research results reveal that dispute resolutions through an adat institution are deemed effective in settling conflicts because the law was made on the basis of the nature of adat communities and conflicts are settled by a tribal leader who treats people humanely. With stages of deliberation and the wisdom demonstrated by the tribal leader that adheres to ancestral values, reconciliation, and peace can take place holistically and fast, without rejection and prejudice. However, dispute resolutions with the help of adat institutions need improving, entailing institutional strengthening, regular coordination between the adat dispute resolution institutions and law enforcers, meaningful participation, and evaluations.